Whatsapp-based exercise training programme for older adults with musculoskeletal pain and their quality Of life in the community - Che Hasan, Muhammad Kamil; Nik Mohd Hatta, Nik Noor Kaussar; Jamaludin, Thandar Soe Sumaiyah; Mat Nasir, Muhamad Asyraf; Ounjaichon, Sasiporn (2021)
Background: Musculoskeletal pain among older people living in the community increases globally and significantly impact the quality of life. This study aimed to evaluate the potential effect of WhatsApp-based exercise-based programme on musculoskeletal pain and the quality of life of older adults in the community. Method: A quasi experimental study was conducted among older adults 60 years old and above having musculoskeletal pain, mentally intact and living in the East Coast region peninsular Malaysia through convenient sampling. A WhatsApp-based Exercise Training Module for Senior Citizen was developed emphasises on the specific exercises, strength training with and without weight, flexibility exercise and balancing exercise. This module was established to reduce musculoskeletal pain in order to improve quality of life of the older adults. The outcomes were self-reported musculoskeletal pain score and functional limitation measured before and after six weeks of intervention from January to April 2021. Results: There is a significant association of musculoskeletal pain between pre and post-test with a p-value of 0.003(p<0.05). There were no associations between WhatsApp-based exercise training module and quality of life of older adults with a p-value of 0.951(p<0.05); and musculoskeletal pain and quality of life among older people with p-value 0.186 (p<0.05) and rs-value of -4.13. Conclusion: This study provides insight into the feasibility of a Whatsapp-based exercise training programme among older adults with musculoskeletal pain. Further study is worth conducted to determine the potential effectiveness among the community.